Lessons from E-Government Initiatives in Indonesia - Fathul Wahid (Media Informatika, 2004)
E-government has accepted a considerable attention in last few years. Indonesia, like other counties, can take advantages of e-government initiatives, such as to improve transparency, control, and accountability towards implementation good governance. Initial observation through scanning of news on mass-media, similar phenomenon is also found in Indonesia. What are obstacles of e-government initiatives? Are there any best practices to eliminate the degree of the failure? Organizational and cultural inertia, financial constraints, and low ICT penetration, lack of ICT skills are of identified obstacles of e-government implementation. Leadership with a clear vision, partnership with third parties, human resource and infrastructures improvement are some strategies can be offered to cope with the obstacles.